Kontribusi Inovasi Berkelanjutan terhadap Peningkatan Daya Saing Perusahaan di Pasar Internasional - Ronaldo Aprili (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This research aims to explore the role of sustainable innovation in enhancing the competitiveness of companies in the global market. Sustainable innovation is defined as the process of developing and implementing new products, services, and processes that meet the needs of the present without compromising the ability of future generations to meet their own needs. The study employs a mixed-methods approach, combining qualitative and quantitative data from a sample of 100 companies across various industries. The findings indicate that sustainable innovation significantly contributes to a company's market position, profitability, and resilience.